The impact of private international donor foundations on sexual and reproductive health organisations in South Africa - Kuhnert, Kira-Leigh (Department of Political Studies, 2014)
Foundations can subtly redefine or steer organisations in a desired direction, through either bureaucratic 'cherry-picking' the organisations that they want to work with - which could be solicited to submit funding proposals;; or over-time professionalising the organisation and providing capacity-building and skills development, placing the organisation in a new context (Bartley;; 2007: 229). Recent actions by bilateral and independent donors to downsize or withdraw funding from South African civil society, has resulted in the closure of some non-governmental organisations, and placed financial pressure on whole sectors in civil society. These developments have created a renewed interest into the funding relationships and impact of donors on non-governmental organisations, and the issues that they represent. This thesis focuses on philanthropic foundations and how, through their operating procedures, they impact grantee organisations and more broadly non-governmental organisations within a specific sector. By understanding the way independent donors, through their foundations, operate and disburse funding, one can gain insight into how relationships with grantees develop and donors are able to influence the agenda-setting. This thesis provides an overview of philanthropy and the impact it has had on the sexual and reproductive health sector in South Africa, in particular. In so doing, a brief background on the funding history by independent and bilateral donors to South Africa is given. This highlights a close relationship between civil society and foreign based funders. The historical reliance by civil society on independent donors, and the small pool of donors active in funding to sexual and reproductive health rights creates an environment in which organisations that are operating in the sector are influenced by the direction and mission of the donor foundations.